ANALISIS POTENSI BAHAYA DENGAN MENGGUNAKAN METODE HIRA (HAZARD IDENTIFICATION AND RISK ASSESSMENT) PADA PABRIK ROTI TAWAR X BOYOLALI - Sekar Larasati; Suroto Suroto; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
HIRA (Hazard Identification and Risk Assessment) is one of the risk assessment methods used to assess hazards that can pose the greatest risk taking into account how likely it is and how big an impact it is. This study was conducted to identify potential hazards, conduct risk assessments, and describe existing hazard control and provide recommendations on control efforts to reduce the risk of work accidents at the X Boyolali Bread Factory. This research is qualitative research by conducting in-depth interviews with six main informants and making the HIRA table as a triangulation. The working process of this factory includes dough making, roasting, and packaging parts. Based on the research found several potential hazards, namely soreness or pain resulting from repeated movements, slippery floors, electrocution, exposed to a roasting machine, dehydration, exposure to peelers, and fire. Control efforts that have been carried out by the owner, namely engineering techniques on paring machines, providing information related to operational standards of work, the implementation of rest hours and holidays, as well as the provision of PPE to workers.